Neuroleptic Malignant Syndrome – A medical emergency in a psychiatric patient (Bangladesh Critical Care Journal, 2018)
With an estimated incidence of 0.02 to 3.23%1, neuroleptic malignant syndrome (NMS) is a rare idiosyncratic reaction to antipsychotic drugs; having a relatively high fatality rate of about 10%2. Here, we are reporting, a 38 years old female schizoaffective patient, presented with fever, muscle rigidity and altered sensorium who had started tablet risperidone(an atypical antipsychotic drug) 11 days prior to hospital admission. After initial sepsis work up and neuroimaging, infective causes and acute cerebrovascular incidents were ruled out and a presumptive diagnosis of NMS was made. Immediate discontinuation of suspected causative agent, along with the provision of supportive care leads to complete resolution of all the symptoms in our patient.Bangladesh Crit Care J September 2018; 6(2): 108-110